Characteristics of SlCML39, a Tomato Calmodulin-like Gene, and Its Negative Role in High Temperature Tolerance of Arabidopsis thaliana during Germination and Seedling Growth - Haidong Ding (MDPI AG, 2021)
Calmodulin-like (CML) proteins are primary calcium sensors and function in plant growth and response to stress stimuli. However, so far, the function of plant CML proteins, including tomato, is still unclear. Previously, it was found that a tomato (Solanum lycopersicum) CML, here named SlCML39, was significantly induced by high temperature (HT) at transcription level, but its biological function is scarce. In this study, the characteristics of SlCML39 and its role in HT tolerance were studied. SlCML39 encodes a protein of 201 amino acids containing four EF hand motifs. Many cis-acting elements related to plant stress and hormone response appear in the promoter regions of SlCML39. SlCML39 is mainly expressed in the root, stem, and leaf and can be regulated by HT, cold, drought, and salt stresses as well as ABA and H2O2. Furthermore, heterologous overexpression of SlCML39 reduces HT tolerance in Arabidopsis thaliana at the germination and seedling growth stages. To better understand the molecular mechanism of SlCML39, the downstream gene network regulated by SlCML39 under HT was analyzed by RNA-Seq. Interestingly, we found that many genes involved in stress responses as well as ABA signal pathway are down-regulated in the transgenic seedlings under HT stress, such as KIN1, RD29B, RD26, and MAP3K18. Collectively, these data indicate that SlCML39 acts as an important negative regulator in response to HT stress, which might be mediated by the ABA signal pathway.